Politics, Poetry, People: an Overview of Contemporary Poetry Trends in the British Literary Landscape - Zimina, Evgeniia; Sargsyan, Mariana (Armenian Folia Anglistika, 2019)
The article deals primarily with the poetic discourse surrounding the 2014 Scottish Independence Referendum and the post-referendum developments in the UK. The political processes of the recent years have been unprecedented in terms of the public resonance, which was by and large due to the active involvement of the social media. By examining the language and rhetoric strategies used in poems we become aware of the message behind them, of the political ideologies they are based on and of the means employed to address the public. It is argued that poetry, whether traditional or digital, sentimental or furious, played and still continues to play a significant role in shaping debate over mega political processes in the UK and in affecting people’s opinion.
Keywords: 2014 Scottish Independence Referendum; Brexit; nationalism; politics; poetry; social media; amateur authors